2014
DOI: 10.3844/jcssp.2014.1692.1702
|View full text |Cite
|
Sign up to set email alerts
|

A User Protection Model for the Trusted Computing Environment

Abstract: Information security presents a huge challenge for both individuals and organizations. The Trusted Computing Group (TCG) has introduced the Trusted Platform Module (TPM) as a solution to end-users to ensure their privacy and confidentiality. TPM has the role of being the root of trust for systems and users by providing protected storage that is accessible only within TPM and thus, protects computers against unwanted access. TPM is designed to prevent software attacks with minimal consideration being given towa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The TPM-UAM model was presented and evaluated qualitatively using the focus group approach, where a group of experts evaluated the proposed model and confirmed the model efficiency (Alshar'e et al, 2014). In this paper we introduced the design and the Implementation of the TPM-UAM model.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The TPM-UAM model was presented and evaluated qualitatively using the focus group approach, where a group of experts evaluated the proposed model and confirmed the model efficiency (Alshar'e et al, 2014). In this paper we introduced the design and the Implementation of the TPM-UAM model.…”
Section: Resultsmentioning
confidence: 98%
“…In order to solve the problem, we proposed a user protection Model is proposed for the trusted computing environment (Alshar'e et al, 2014) and it has been demonstrated that the TPM user authentication model is a solution to overcome weaknesses within the TPM and to provide a solid basis for authenticating and confirming the identity of the user, thus protecting the TPM from unwanted access and keeping it safe against Evil Maid and other similar attack mechanisms until verification of the user has been completed.…”
Section: Introductionmentioning
confidence: 99%
“…Universities are unwilling to invest in technology without such assessments. As a result, there are no objective definitions of success in the development process, which stymies growth [9][10][11][12][13][14][15]. As a result, the current research will look at the applicability of DeLone and Mclean's concept to different cultures, particularly Jordan's.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the findings of this study, which aims to broaden comparative assessments of using Dealone and Mclean's model in developing nations, will assist other research studies exploring cross-cultural aspects and those in the meta-assessment field. This study also aims to determine the significance of technological attitudes and their relationships with VR-learning intent, usage, user satisfaction, and net benefits [10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Information security management (ISM) is a systematic preservation approach to protect the integrity, confidentiality, availability, authenticity, reliability and accountability of information [1], [2], [3]. Every single day, organisations and their information are exposed to security threats and incidents such as malware, virus, malicious spyware, spam, phishing and sabotage from an extensive range of sources [4], [5], [6], [7]. Researches have indicated that security incidents increase over the years [8].…”
Section: Introductionmentioning
confidence: 99%